High intensity aerobic interval training: necessary but insufficient for optimal endurance performance? - Seiler, S. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
The athlete´s laboratory is daily training, month after month. The outcome variable is performance. This Darwinian arena sets the stage for a self-organizing process of training optimization based on thousands of athlete-year iterations of the same"experiment" connecting training input and performance outcome. How do elite endurance athletes train? Descriptive studies from divergent sports competed over 4-120 min show remarkable consistency in a key training characteristic; about 75 to over 90% of endurance sessions / km / HR zone minutes are typically performed at intensity under VT1, or =2mM blood lactate (LSD). Billat et al. (1) reported that elite marathoners (2:06-2:12), performed 75% of their training kms as LSD, 4% at their lactate threshold (race intensity), and 20% above LT. About 85% of the training distance of elite Kenyan 10k runners is actually LSD (2). Elite rowers, who compete over ~6 minutes at ~100% VO2 max intensity, perform 80% or more of endurance training time at = 2mM blood lactate (5, 10). Data from other sports concur (7,8). All of these groups also perform HIT, and often temporarily increase HIT loading in peaking periods, but clearly emphasize large volumes of LSD throughout the training year. Training studies on athletes Esteve-Lanao et al (4) compared performance changes in sub-elite runners after 20 weeks of training with either 80-12-8 % or 67-25-8% distribution of training below VT1, between VT1 and VT2, and over VT2. The athletes performing more LSD training improved 10.4 km cross-country time more (157 ± 21 vs 121± 13 seconds, p<0.05) than the "threshold training" group. After a 25 day detraining period at <10% full training, 18 national class rowers trained for 12 weeks, either "100% LSD" training (64-74% VO2 peak, n=9, LOW)) or 70% below LT and 30% between 84 and 100% VO2 peak (MIX, n=9). Performance and VO2peak improvement were significant but similar in LOW and MIX. Power at LT and at 4mM [La-] increased more in LOW (6). Stress Avoidance or Adaptive Signalling Advantage? Potential driving mechanisms for the emphasis on LSD in top performers may be based on substituting duration for intensity in order to minimize stress responses and overtraining risk (3, 9). Alternatively, low intensity, longer duration training alone or in combination with energy status may elicit cell-signalling advantages that promote greater muscular adaptation. Perhaps it is both.